All Days 1991
DOI: 10.4043/6758-ms
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of the UOE Manufacturing Process on the Collapse Pressure of Long Tubes

Abstract: A commonly used process for manufacturing large-diameter tubes for offshore pipeline, riser and tension-leg platform tether applications, involves the cold forming of long plates. The plates are bent into a circular shape and then welded. The circumference of the pipe is then plastically expanded to develop a high tolerance circular shape. Collectively these steps compriee the U-O-E manufacturing process. These mechanical steps cause changes in the material properties and introduce residual stresses in the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Typical larger diameter pipes are manufactured by a process known as UOE, where a long plate is formed into a circular shape, longitudinally welded, then radially plastically expanded (cold expanded) to achieve a uniform diameter. Kyriakides and Corona (1991) and Shoemaker (1984) provide good summaries of the effects this process has on reducing pipe circumferential compressive material strength. Williams and Elsea (1977) also provide a good summary of this reduction, which can be attributed to the Bauschinger effect.…”
Section: Manufacturing Processesmentioning
confidence: 99%
“…Typical larger diameter pipes are manufactured by a process known as UOE, where a long plate is formed into a circular shape, longitudinally welded, then radially plastically expanded (cold expanded) to achieve a uniform diameter. Kyriakides and Corona (1991) and Shoemaker (1984) provide good summaries of the effects this process has on reducing pipe circumferential compressive material strength. Williams and Elsea (1977) also provide a good summary of this reduction, which can be attributed to the Bauschinger effect.…”
Section: Manufacturing Processesmentioning
confidence: 99%
“…Following, some important publications referred to UOE manufacturing process are mentioned. An initial study on the effects of the UOE process on the mechanical behavior has been reported by Kyriakides et al [2] using a simple analytical model. It has been shown for the first time that the cold forming of line pipes has a significant effect in determining the level of residual stresses in a line pipe, and should be taken into consideration for the prediction of 1 the ultimate external pressure and pressurized bending capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the larger Mardi Gras pipelines (diameters greater than 16-inch) had to be manufactured by the UOE forming process, which reduces the hoop compressive yield stress, and hence the collapse resistance (Kyriakides et al (1991)). …”
Section: Pipeline Collapse Testingmentioning
confidence: 99%